Spectrophotometric Determination of Pd(II) Using 4-Methyl Benzaldehyde Oxime - LOKHANDE, R.S.; PATIL, UJWALA (Asian Journal of Chemistry, 2010)
Spectrophotometric method has been developed for the determination of palladium(II) using 4-methyl benzaldehyde oxime as a reagent. The reagent reacts with Pd(II) giving yellow coloured complex which can be quantitatively extracted in butanol at pH 6.0. Molar absorptivity at 415 nm is 0.8857 x 102 L mol-1 cm-1. Beer's law is obeyed in the range of 1 to 12 ppm. The present method has been used for analysis of Pd(II) in silver alloy and palladium catalysts.